Clustering and Modeling of E-Government Architecture Using the Algorithm C4.5 - Sefri Yansyah (Jurnal Informasi dan Teknologi, 2023)
E-Government is a form of government service effort to present complete, easily accessible, updated and high-accuracy data to the public. Good Governance is the aspiration of the Pelalawan Regency Government so that the service becomes a government administration that prioritizes aspects of accountability, transparency and accountability. participatory, Assist in identification efforts and then become a solution to solving problems where so far the Pelalawan District Government programs are often not on target, data gaps and the dynamic nature of data from time to time. This is caused by the large number of information systems facilitated by Ministries, Agencies and other Institutions for use by Regional Apparatus Organizations that are not relevant to the variables and data criteria that are suitable to be applied to Pelalawan Regency, considering the data that has been processed so far is very large and large. Solution Method C4.5 can assist in identification efforts and then become a problem solving solution where so far the Pelalawan District Government program is often not right on target, data gaps and the dynamic nature of data from time to time. The data used in this study are 3 information systems facilitated by the Ministry of Social Affairs, Visualization and Analysis, a collection of data with different and growing formats is then clustered using the C.45 method by carrying out the Big Data principles, namely volume, velocity, variety, varicity and value. This research will later become input to the Regional Government in determining decisions on the implementation of assistance to the poor which refers to the indicators from this data mining.